THE EFFECTS OF GLOBAL DYNAMICS TO URBAN HIERARCHY: COMPROMISING CITIES INSTEAD OF COMPETITIVE CITIES - Elif Ornek Ozden; Ebru Seckin; Senem Kozaman (European Regional Science Association (ERSA), 2011)
Especially after 1990's, important results have emerged with the rapid transformation process in the world by the concept of globalization. It is emphasized that cities are the center of spatial transformation where the globalization mostly effected. The economic and technological developments have caused the fluidity of capital in this manner cities have to bring out their potentials more than ever to attract the capital and disparities reveals in the pattern of urban hierarchy. The presence of cities depends on the renewal of existing potentials according to the changing conditions of today. In this process, many cities around the world, especially with economic, spatial, environmental advantages come forward in the international arena. While the competition between cities significantly increased, the cities that cannot keep up with varying conditions are destined to lose. The context of this paper is about the effects of the globalization and changes in the economic structure to urban hierarchy which is examined in the Aydın Providence of Turkey. Aydın is a developed province of Aegean Region which is situated in the seaside with its natural amenities that has to be protected. There are sub-regions which have different identities stands out in the province. The settlements in the inner sides and the coast sides differentiate in social, economic, demographic characteristics. While the population of settlements in the coast side of the province are increased as a result of investments and tourism potentials, the population of inner settlements which are based on agricultural economies, are decreased. Consequently, a dual structure is present in the very same region; we can see developing and an under developed sub-regions. The material example of this structure can be observed in two different districts of Aydın; Kuşadası which is situated in the seaside; Söke which is situated in the inner side. At this point, the basic problematic of this paper is about the positive-negative effects of rapid development of certain areas. As a result, in the context of emerging problems, the two settlements which are located in close proximity are examined and the concept of compromising cities suggested instead of competitive cities.
Keywords: 330